The Age of Artificial Intelligence: The Effect of Technology- Organization-Environment on Intention to Adopt Robotic Technologies in Hotel Businesses - Baydeniz, Erdem (Indonesian Journal of Sustainability Accounting and Management, 2023)
This study examines the factors influencing hotel managers’ intentions to adopt robotic technologies in the hotel industry. A questionnaire-based survey was conducted among hotel managers in Afyonkarahisar, Antalya, and Izmir Provinces. The survey collected data from 396 participants. The collected data were then analyzed using PLS-SEM to identify the relationships between the factors and adoption intentions. The analysis revealed that technology and organization significantly influence the intention to adopt robotic technologies in hotels. However, the environmental factor was found to have no significant effect on adoption intentions. Understanding the factors that drive adoption intentions can guide the development of effective strategies for implementing robotic technologies in hotels, leading to increased operational efficiency and improved guest experiences. This research contributes to the existing literature by applying the TOE framework to examine the adoption of robotic technologies, specifically in the hotel industry. The IPMA used in this study provides a unique perspective on the relative importance and performance of the influencing factors, which aids in the decision-making process.